Identification and Mitigation of Machining Process Failures in XE 611 SZK Crankshaft through an Integrated FMEA and Pareto Analysis Approach - Ichlas Nur; Rifki Abdul Dhohir; Nasirwan; Nusyirwan4; Yuli Yetri (Journal of Applied Mechanical Engineering and Renewable Energy, 2026)
The quality of the machining process in critical components such as crankshafts plays a significant role in determining engine performance and reliability. This study aims to analyze the causes of failure in the milling and drilling machining processes of the XE 611 SZK crankshaft. The research methods included direct observation of the production process, analysis of machining parameters, and evaluation of machining quality through visual inspection and dimensional measurements. In addition, root cause analysis was conducted using fishbone diagrams and Failure Mode and Effects Analysis (FMEA) to identify the dominant factors contributing to process failures. Furthermore, Pareto analysis was applied to determine the primary causes of failure based on the 80/20 principle. The results indicate that machining failures were mainly caused by tool wear, improper cutting parameters (cutting speed, feed rate, and depth of cut), machine setup errors, and suboptimal coolant system performance. These failures resulted in surface defects, dimensional deviations, and an increased product rejection rate. The proposed recommendations include optimization of machining parameters, implementation of preventive maintenance for machines and tooling, and enhancement of quality control during the production process. This study is expected to serve as a reference for improving machining efficiency and reducing failure rates in the manufacturing industry